(untitled) (Czech Journal of International Relations, 1993)
Jiří Kosta, Judita Stouračová, Michael Konstantinov: Přímé investice z Německa v České republice (Deutsche Direktinvestitionen in der Tschechischen Republik). Friedrich Ebert Stiftung, Praha 1993, 144 stran.